2014
DOI: 10.1021/bi500238q
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Adaptation of Dihydrofolate Reductase from the Moderate Thermophile Geobacillus stearothermophilus

Abstract: The thermal melting temperature of dihydrofolate reductase from Geobacillus stearothermophilus (BsDHFR) is ∼30 °C higher than that of its homologue from the psychrophile Moritella profunda. Additional proline residues in the loop regions of BsDHFR have been proposed to enhance the thermostability of BsDHFR, but site-directed mutagenesis studies reveal that these proline residues contribute only minimally. Instead, the high thermal stability of BsDHFR is partly due to removal of water-accessible thermolabile re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Although δ γ /δ T in TmDHFR has not been determined, it is likely independent of protein isotope labeling since the corresponding enzyme KIE is close to unity for all temperatures. Given that TmDHFR is highly rigid, 67 69 it is reasonable to expect that protein reorganizational motions are minimal even though the electrostatic environment of the active site is not optimal, but additional computational analyses are needed to confirm this. In all of these DHFRs, the experimental activation free energies for the ‘light’ and ‘heavy’ enzymes are statistically the same due to enthalpy/entropy compensation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although δ γ /δ T in TmDHFR has not been determined, it is likely independent of protein isotope labeling since the corresponding enzyme KIE is close to unity for all temperatures. Given that TmDHFR is highly rigid, 67 69 it is reasonable to expect that protein reorganizational motions are minimal even though the electrostatic environment of the active site is not optimal, but additional computational analyses are needed to confirm this. In all of these DHFRs, the experimental activation free energies for the ‘light’ and ‘heavy’ enzymes are statistically the same due to enthalpy/entropy compensation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both BsDHFR 111,124,125 and MpDHFR 12 are more flexible than EcDHFR, yet at pH 7 the three enzymes have similar single turnover rate constants. 12,36 EcDHFR-N23PP/S148A has reduced thermal motion on the millisecond timescale, which impedes the conformational changes required for optimal progression through the catalytic cycle. 24 The increased dynamic coupling to the reaction on the femtosecond-picosecond timescale is detrimental to the chemical step as it increases the proportion of unproductive trajectories on the transition state dividing surface.…”
Section: Discussionmentioning
confidence: 99%
“…104,105 For TmDHFR, EcDHFR, MpDHFR and BsDHFR, viscosity had no effect on the single turnover rate constants at pH 7 and solvent composition did not affect the KIE. 11,12,22,36 In contrast, the dielectric constant of the medium had a pronounced effect on both the single turnover and steady state rate constants at pH 7. Although no viscosity effect on the steady state rate constant was observed for TmDHFR, 22 MpDHFR 12 or BsDHFR, 36 solvents with similar dielectric constants reveal a small, but consistent, effect from viscosity in the steady state for EcDHFR.…”
Section: Active Site Volume and Conformational Samplingmentioning
confidence: 98%
“…It has previously been shown that the L20M variant of DHFR from the thermophile Geobacillus stearothermophilus (BsDHFR) also has kinetics similar to that of the wild-type enzyme. 32 K M values were largely unchanged for the EcDHFR variants but slightly elevated for NADPH in the MpDHFR variants (Supporting Information). The steady state rate constant of wild-type EcDHFR at pH 7 is limited by the release of THF from the E·NADPH·THF mixed ternary complex.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%